Berry Size and Qualitative Characteristics of Vitis vinifera L. cv. Syrah - Barbagallo, M.G.; Guidoni, S.; Hunter, J.J. (South African Journal of Enology and Viticulture, 2011)
The effect of variation in berry size on berry composition was studied in irrigated Syrah/R99 grapevines, located in a temperate area of South Africa. Berries from 45 clusters, sampled from both sides of the canopy (east and west), were weighed to create four categories: 1. less or equal to 1.5 g; 2. between 1.51 g and 2.00 g; 3. between 2.01 g and 2.50 g; 4. more than 2.50 g. Berry physical characteristics were determined and total anthocyanins and seed flavonoids were analysed by spectrophotometry and anthocyanin profiles by HPLC. The ratio of skin weight:berry weight did not change with increasing berry size, but the ratio of seed weight:berry weight increased. For total anthocyanins, varying results were obtained if values were expressed in mg/berry, mg/g skin, mg/kg grape and mg/cm2 skin. The quantity of total anthocyanins changed positively with increasing berry weight if expressed in mg/berry and remained almost similar if expressed in mg/cm2 of skin. In contrast, total polyphenols decreased with berry weight if the values were expressed in mg/kg grape and in mg/g skin. Total anthocyanins expressed in mg/kg grape and in mg/g skin were correlated positively to the number of berries as well as to the total skin surface in one kilogram of grape. In this study, the largest berries seemed to have lower quality characteristics. In order to obtain better wine quality, it seems important to reduce berry weight and, in general, berry size variability of Syrah. The obtainment and continuity of a particular wine style may be affected by berry variability.